New maps relative to the special protection area of the “palude di Torre Flavia” (central Tyrrhenian Sea - Italy) prone to severe coastal erosion - Davoli, Lina; Raffi, Rossana; Baldassarre, Maurizio Alessio; Bellotti, Piero (Italian journal of engineering geology and environment, 2019)
<span data-sheets-value="{"1":2,"2":"This paper is aimed at Palude di Torre Flavia (SPZ IT 6030020) within the Natura 2000 Network including a coastal sector of central Tyrrhenian Sea (Italy) located about 35 km to the NW of Rome along the right sector of the Tiber River Delta, Italy. This site has a high naturalistic value because it includes a wetland area today threatened in particular by coastal erosion and partly by climate change in progress.\rThe analysis of the shoreline evolution shows that in the past, the wetland should be wider than the current one and, during the time, it was susceptible to an ongoing reduction due to a prevailing erosive trend. This erosive character resulted in reduced backshore width and the steepening of the shoreface. Seasonal morphological profiles show that the winter profile resembles much more a summer beach profile, while the summer profile is in part characterized by winter features. This anomalous climate regime occurring during 2017 belongs to a series of climate irregularity occurring in the last years along the Italian peninsula that testify an ongoing climate change at global scale. Two objectives are proposed: i) understanding the coastal dynamics processes that induce erosion phenomena; ii) editing the geomorphological map using the ISPRA-AIGeo legend recently applied for several Italian coastal sites. It is proposed to identify, characterize and map the forms of the coastal landscape with the purpose of providing a useful tool to evaluate the coastal hazard and to support future land planning and management."}" data-sheets-userformat="{"2":15297,"3":{"1":0},"9":0,"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">This paper is aimed at Palude di Torre Flavia (SPZ IT 6030020) within the Natura 2000 Network including a coastal sector of central Tyrrhenian Sea (Italy) located about 35 km to the NW of Rome along the right sector of the Tiber River Delta, Italy. This site has a high naturalistic value because it includes a wetland area today threatened in particular by coastal erosion and partly by climate change in progress. The analysis of the shoreline evolution shows that in the past, the wetland should be wider than the current one and, during the time, it was susceptible to an ongoing reduction due to a prevailing erosive trend. This erosive character resulted in reduced backshore width and the steepening of the shoreface. Seasonal morphological profiles show that the winter profile resembles much more a summer beach profile, while the summer profile is in part characterized by winter features. This anomalous climate regime occurring during 2017 belongs to a series of climate irregularity occurring in the last years along the Italian peninsula that testify an ongoing climate change at global scale. Two objectives are proposed: i) understanding the coastal dynamics processes that induce erosion phenomena; ii) editing the geomorphological map using the ISPRA-AIGeo legend recently applied for several Italian coastal sites. It is proposed to identify, characterize and map the forms of the coastal landscape with the purpose of providing a useful tool to evaluate the coastal hazard and to support future land planning and management.